Effects of uric acid on vascular endothelial function from bedside to bench. Issue 11 (November 2018) - Otani, Naoyuki; Toyoda, Shigeru; Sakuma, Masashi; Hayashi, Keitaro; Ouchi, Motoshi; Fujita, Tomoe; Anzai, Naohiko; Tanaka, Atsushi; Node, Koichi; Uemura, Naoto; Inoue, Teruo
Abstract This study was designed to investigate the effects of uric acid on vascular endothelial function in measurements carried out either at the bedside or the laboratory bench. First, we performed reactive hyperemia peripheral arterial tonometry using an EndoPAT 2000 device and measured serum uric acid levels in 92 outpatients with hypertension. The reactive hyperemia index (RHI) showed no correlation with serum uric acid level (R  = −0.125, P  = 0.235) in either overall patients or in a high-risk group of 51 patients with complications such as cardiovascular and cerebrovascular diseases, chronic kidney disease, and/or diabetes (R  = −0.025, P  = 0.860). However, in the remaining 41 patients in the low-risk group, RHI correlated negatively with serum uric acid level (R  = −0.335, P  = 0.032). Multiple regression analysis showed that serum uric acid level predicted RHI (R  = −0.321, P  = 0.043) in the low-risk group independent of age, body mass index, systolic blood pressure, and low density lipoprotein-cholesterol level. We then performed an in-vitro study using the WST-8 assay in human umbilical vein endothelial cells, which showed that hypoxic conditions reduced cell viability. Treatment with uric acid caused a further reduction in cell viability, while ascorbic acid improved viability. Using Western blot analysis, we observed that uric acid reduced endothelial nitric oxide synthase phosphorylation during hypoxic conditions. Serum uric acid level is associated with peripheral vascular endothelial function in patients with low-risk hypertension and uric acid could directly impair endothelial function under hypoxic conditions. These results are relevant to the interventional studies examining the cardiovascular protective effect of hypouricemic agents.